PERSEPSI MAHASISWA TENTANG PENGGUNAAN SMART CLASSROOM DALAM PEMBELAJARAN ATLETIK - Nurafiati, Suastika; Herman, Herman; Angriawan, Tri; Suparman, Suparman (Indonesia Sport Journal, 2024)
The use of technology in learning in this era is very important. The existence of technology-based learning facilities and tools such as smart classrooms make learning more effective. Athletics courses which are synonymous with practical learning and carried out in the field can be integrated with platform learning on smart class features. The purpose of this research is to determine student perceptions regarding the use of smart classrooms in learning athletics courses. This research was conducted using qualitative descriptive research methods. The research technique was carried out by collecting data through direct interviews and classroom observations. The respondents in this research were 1st semester students of the Physical Education, Health and Recreation Study Program, STKIP YPUP Makassar. Based on the results of field research, it is stated that student perceptions regarding the use of smart classrooms in learning athletics courses provide new experiences for students. Students responded positively about the use of smart classrooms. Overall, the results of this research state that students are more active in interacting and independent in accessing their new knowledge. Students are more motivated to take athletic courses conducted through the smart classroom. The use of smart classrooms in learning is an innovation in developing technology-based learning. use of technology in learning in this era is very important. The existence of technology base learning facilities and tools such as smart classrooms make learning much more effective.